The Influence of Service Quality, Price, and Marketing Strategy on Consumer Satisfaction at Rezky Car Spare Parts in North Labuhanbatu - Ramadhan Sipahutar, Rezky; Asyiah Siregar, Nurintan; Zelibu, Yanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This study aims to analyze the influence of service quality, price, and marketing strategy on customer satisfaction at Rezky Car Spare Parts in North Labuhanbatu. The background of this study is the importance of understanding the factors that influence customer satisfaction as a basis for increasing loyalty and business competitiveness. The research method used is a quantitative method with a survey approach. Data were collected through questionnaires distributed to consumers, then analyzed using multiple linear regression analysis. The results of the study indicate that partially and simultaneously, service quality, price, and marketing strategy have a positive and significant effect on customer satisfaction. Among the three variables, marketing strategy has the most dominant influence on the level of customer satisfaction. This finding indicates that the company needs to redesign its strategies, run attractive promotions, and improve service quality to achieve optimal customer satisfaction.